Evropa-Aziia . Evropa-Aziia . Europe-Asia . Европа-Азия - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. On the culture and history of Orenburg: an interview with the artist George Barabash, grandson of the governor of Orenburg; the village peoples' choir, Dedurovka (Orenburg region); archaeological excavations in the region with the participation of American Scientists. О культуре и истории Оренбурга: интервью с художником Георгием Барабашем, внуком губернатора Оренбурга; народный хоровой коллектив поселка Дедуровка (Оренбургская область); археологические раскопки в Оренбургской области при участии американских ученых.